Representasi konflik dalam Film Mencuri Raden Saleh - Alifia, Hafidzatu Taslima; Harini, Yostiani Noor Asmi (Universitas Lampung, 2023)
This research aims to explain how the characters in the movie Mencuri Raden Saleh by Angga Dwimas Sasongko experience social events and conflicts. Ralf Dahrendorf's conflict theory can be used to identify social conflicts. The data used is taken from movie footage that illustrates social conflict. The research method used is a descriptive qualitative method. In addition, researchers used the listening method in collecting data. This research results in that all conflicts in the movie are caused by the injustice of the ruling party as the holder of power from the ruling party. Conflicts occur between Piko and her friends with the police, Fela with the car driver, friendship, Piko's father with Permadi, Piko with her father, and Sarah with Permadi's men. All of these conflicts originate from the former President, Permadi. The implication of this research is that what Piko did is the same as what some people experienced during the New Order era. To obey the will of the Supreme Father, he will do anything, including committing crimes. If we dare to refuse, don't expect our safety and that of our families to be protected. After conducting this research, there are limitations in using Ralf Dahrendorf's conflict theory, namely not maximizing or exploring the theory. Suggestions for future research are to try to use other theories to be more varied.Keywords: film, conflict, painting, representation